Application of Polymer Membranes for a Purification of Fuel Oxygenated Additive. Methanol/Methyl Tert-butyl Ether (MTBE) Separation via Pervaporation: A Comprehensive Review - Pulyalina, Alexandra (Polymers (Basel), 2020)
Methyl Tert-butyl Ether (MTBE) remains the most popular fuel additive to improve fuel performance and reduce the emission of hazardous components. The most common method of MTBE production is a catalytic synthesis with a great excess of methanol to improve the reaction yield. The problems of obtaining pure MTBE from the final product have determined the search for new techniques; primarily membrane methods. Pervaporation as an optimal membrane process for highly selective separation of organic mixtures is of particular interest. This review is focused on analysis of the research works on the various polymer membranes and their efficiency for the separation of the azeotropic methanol/MTBE mixture. Currently the most popular materials with optimal transport properties are poly(vinyl alcohol), cellulose acetate and polyheteroarylenes. Mixed matrix membranes (MMM) are highly effective as well as they show overall operational stability.